EXPLORING THE UNEXPECTED EFFECTS OF ARTIFICIAL INTELLIGENCE APPLICATIONS ON STUDENT MOTIVATION FROM THE PERSPECTIVE OF COLLEGE STUDENTS WITHIN THE GREEN LINE - Awawdy, Maison (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
In an attempt to improve the whole college student experience, higher education has adopted modern techniques and technologies more and more in recent years. A few instances of how technology improves college students' educational planning and participation include the usage of games, learning management systems, virtual and augmented reality, artificial intelligence applications, and video-assisted learning. There are worries about how technology may affect students at colleges, universities, and other higher education institutions, despite the fact that it has significantly improved education.